Prevention of soccer injuries: A prospective intervention study in youth amateur players - Junge, A.; Rosch, D.; Peterson, L.; Graf-Baumann, T.; Dvorak, J. (The American Journal of Sports Medicine, 2002)
BACKGROUND: Risk factors for soccer injuries and possibilities for prevention have been discussed by several authors, but only a few have investigated the effectiveness of preventive interventions. PURPOSE: The aim of the present study was to evaluate the effects of a prevention program on the incidence of soccer injuries in male youth amateur players. STUDY DESIGN: Prospective controlled intervention study. METHODS: Seven soccer teams took part in a prevention program that focused oneducation and supervision of coaches and players, while seven other teams were instructed to train and play soccer as usual. Over 1 year all injuries were documented weekly by physicians. Complete weekly injury reports were available for 194 players. RESULTS: The incidence of injury per 1000 hours of training and playing soccer was 6.7 in the intervention group and 8.5 in the control group, which equates to 21% fewer injuries in the intervention group. The greatest effects wereobserved for mild injuries, overuse injuries, and injuries incurred during training. The prevention program had greater effects in low-skill than in high-skill teams. CONCLUSIONS: The incidence of soccer injuries can be reduced by preventive interventions, especially in low skill level youth teams. Coaches and players need better education regarding injury prevention strategies and should include such interventions as part of their regular training.